PENGEMBANGAN EKOWISATA RIVER TUBING PADA DESTINASI GATEP LAWAS BERBASIS MASYARAKAT DI DESA AMBENGAN KECAMATAN SUKASADA KABUPATEN BULELENG - Desi Aryani, Luh (UHN IGB Sugriwa Denpasar, 2026)
River Tubing ecotourism is one of the tourist attractions at the Gatep Lawas destination managed by KUPS. River Tubing ecotourism is a tourist attraction that offers activities that are not usually carried out by tourists in general or tourism that requires courage or special interest to do it. As time went by, the Covid-19 pandemic hit Indonesia in 2020, so the River Tubing ecotourism attraction stopped and after the pandemic it started to be developed again. The analysis shows the potential for river tubing ecotourism at Gatep Lawas, which is categorized into three types: natural and man-made. Community participation in river tubing ecotourism development, from planning, implementation, management, and evaluation, has involved the local community, inviting them to participate in the management of Gatep Lawas. However, public awareness campaigns are still lacking, as only a small portion of the community understands the emerging tourism landscape. Analysis with the SWOT matrix produces SO (strength opportunity) strategy, namely optimizing the River Tubing ecotourism attraction, ST (strength threats) strategy, namely developing human resources, increasing the competitiveness of attractions, WO (weakness opportunity) strategy, namely providing education, training counseling on ecotourism or the tourism sector to the community, WT (weakness threats) strategy conducting comparative studies to attractions that have developed ecotourism in collaboration with travel agents and regional tourism offices. Key words: ecotourism, River Tubing, community